2014
DOI: 10.1007/s11259-014-9602-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of porcine NLRP3 inflammasome activation and its upstream mechanism

Abstract: Inflammasomes, which are intracellular sensors of endogenous or exogenous danger signals, activate caspase-1, resulting in interleukin (IL)-1β maturation. Although most studies on inflammasomes have been performed in human and/or mouse-derived macrophages, porcine inflammasome activation has not been elucidated even though pigs are considered one of the best animal models for translational and preclinical investigations. In this study, we optimized detection of porcine IL-1β secretion, which is the most well e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…As far as we know, plenty of evidence suggested that PI3K signaling plays a pivotal role downstream of oxidative stress in airway inflammation (Marwick et al, 2009) and in pulmonary epithelial cells (Papaiahgari et al, 2006). Oxidative stress was an vitally important mechanism involved in TDI induced asthma (Shin et al, 2013) as well as the most well-established upstream of caspase-1 (Kim et al, 2014). Therefore, it is possible that ROS/PI3K signal pathway mediates TDI induced caspase-1 activation, which deserves our future investigation.…”
Section: Discussionmentioning
confidence: 93%
“…As far as we know, plenty of evidence suggested that PI3K signaling plays a pivotal role downstream of oxidative stress in airway inflammation (Marwick et al, 2009) and in pulmonary epithelial cells (Papaiahgari et al, 2006). Oxidative stress was an vitally important mechanism involved in TDI induced asthma (Shin et al, 2013) as well as the most well-established upstream of caspase-1 (Kim et al, 2014). Therefore, it is possible that ROS/PI3K signal pathway mediates TDI induced caspase-1 activation, which deserves our future investigation.…”
Section: Discussionmentioning
confidence: 93%
“…In pigs, it is not different from that in humans or mice. 27 The NLRP3 inflammasome is now recognized as a critical molecular mechanism for many degenerative diseases. 27 Several models have been developed to describe how NLRP3 inflammasomes are activated, including K + efflux, lysosome function, ER stress, intracellular calcium, ubiquitination, microRNAs and, in particular, ROS.…”
Section: Discussionmentioning
confidence: 99%
“…For inflammasome activation, BMDMs (1.0 × 10 6 cells per well) in RPMI 1640 containing 10% FBS and antibiotics were seeded in 12-well tissue culture plates (SPL Life Science Co.) and primed with lipopolysaccharide (LPS, 1 μg/mL; #L4130, Sigma-Aldrich Co., St. Louis, MO, USA) 43, 44 . After 3 h, LPS-primed BMDMs were given fresh media (RPMI 1640, 350 μL in 12-well plates) without FBS or antibiotics in the presence of adenosine triphosphate (2 mM, ATP; #tlrl-atp, InvivoGen, San Diego, CA, USA) for 1 h, nigericin (40 μM, NG; #4312 Tocris Bioscience, Bristol, UK) for 1 h, flagellin (0.5 μg/mL; #tlrl-stfla, InvivoGen) with Lipofectamine 2000 (10 μL/mL, Invitrogen, Grand Island, NY, USA) for 1 h, double-stranded DNA (1 μg/mL, dsDNA) with jetPRIME TM (2 μL/mL, Polyplus-transfection Inc., Illkirch, France) for 1 h, monosodium urate crystals (800 μg/mL, MSU, Sigma-Aldrich Co.) for 6 h, LPS (14 μg/mL) with Lipofectamine 2000 (10 μL/mL) for 6 h, or Escherichia coli ( E .…”
Section: Methodsmentioning
confidence: 99%